Perspectives of chemical education in universities of technical profile (Pedagogy of Higher and Secondary Education, 2013)
Chasova E. V., Ivchuk V. V. Perspectives of chemical education in universities of technical profile.The article led the main trends of chemical education at the universities of technical profile. The role of quality assurance in higher education, as an essential condition for innovative development in the career-oriented education.
Keywords: chemical education; non-chemical specialties; technical universities; the forms of the educational process; axiology